Place of injuries of elbow joint in the structure of primary permanent disability among Ukrainian population - L.Y. Naumenko; T.O. Zub; A.O. Mametyev (Medičnì Perspektivi)
Despite the rapid development of orthopedics consequences of elbow injuries have a significant proportion of unsatisfactory treatment results until now. Owing to comprehend the sources of disability doctors could determine drawbacks of treatment and regulate rehabilitation program for patients with elbow injuries better. The purpose of the study was to investigate the structure of primary permanent disability due to elbow injuries among the Ukrainian population. The study was made on annual reports of Regional centers of medical and social expertise and the Center of medical and social expertise of the city of Kiev for 2018. During the reporting period a disability group due to upper extremity injuries was established totally for 1 211 patients in age over 18 years, among them 195 people had consequences of elbow traumas. That caused an intensive prevalence rate of 6.22 cases per 1 million of adults. Male patients (70.8%) and patients in working age (94.9%) prevailed among people with disability. 10.8% of patients were determined as people with disability without a revision period after the primary examination on medical and social expertise commission. The causes of primary permanent disability were domestic injuries (90.8%), occupational injuries (5.0%), injures during military service and battle injuries (2.1%) and disability since the childhood (2.1%). Structure according to disability groups showed the next distribution: 90.3% – the 3rd group, 9.2% – the 2nd group and 0.5% – the 1st group. Consequences of elbow injuries which led to primary permanent disability were caused by bone fractures (61.5%), elbow contractures and elbow ankyloses (19.0%), injuries of an ulnar nerve (8.7%), traumatic amputation at the elbow level (6.2%), forearm dislocations (3.1%), open wounds of elbow (1.0%), elbow ligaments ruptures (0.5%). Patients registered as disabled with a revision period during the first examination on commission had sufficient rehabilitation potential for restoration of elbow joint function and one of the upper limb in total.